How to hide an empire a history of the greater United States - Immerwahr, Daniel 1980- (Farrar, Straus and Giroux, 2019)
"A history of the United States' overseas possessions, from Puerto Rico to the Philippines and beyond, and what they reveal about the true meaning of American empire."--Provided by publisher.